LINGUO-PRAGMATIC FEATURES OF ONOMATOPOEIC UNITS IN ENGLISH AND UZBEK LANGUAGES (International journal of artificial intelligence, 2024)
Onomatopoeic units are words that represent sounds, actions, or events, the meaning of which is related to the sounds. Onomatopoeic units in English and Uzbek languages ​​have their own linguopragmatic properties. This article analyzes the linguo-pragmatic features of onomatopoeic units in English and Uzbek languages, their use and their place in the cultural context.